2012
DOI: 10.1097/hjh.0b013e32834f9882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild hyperisulinemia on conduit vessel endothelial function

Abstract: Physiological hyperinsulinemia has no effect on endothelium-dependent vasodilatation in conduit vessels of healthy individuals, but it induces a slight decline in endothelium-independent vasodilatation, which is entirely explained by the insulin-induced noradrenergic activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The augmented responses to nitroglycerine documented in the present cohort may reflect less neurogenic constraint on the dilator capacity of vascular smooth muscle as a result of diminished MSNA. Indeed, in a recent experiment involving 10 healthy male volunteers submitted to a sympathoexcitatory stimulus, the brachial dilator response to nitroglycerine was augmented by intravenous infusion of the centrally acting sympatholytic drug, clonidine 35. As baseline diameter was not increased, an inhibitory effect of simvastatin on vascular Rho kinase activity36 is less likely.…”
Section: Discussionmentioning
confidence: 99%
“…The augmented responses to nitroglycerine documented in the present cohort may reflect less neurogenic constraint on the dilator capacity of vascular smooth muscle as a result of diminished MSNA. Indeed, in a recent experiment involving 10 healthy male volunteers submitted to a sympathoexcitatory stimulus, the brachial dilator response to nitroglycerine was augmented by intravenous infusion of the centrally acting sympatholytic drug, clonidine 35. As baseline diameter was not increased, an inhibitory effect of simvastatin on vascular Rho kinase activity36 is less likely.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of homogenous response is also apparent in studies utilizing low dose insulin. Increased limb blood flow was observed in response to insulin infusion rates 0.06-0.5 mU/kg/min [43, 69,97], whereas other studies reported no effects at similar infusion rates [120,135,191]. Furthermore, blood flow reductions have been observed in response to low (0.2 mU/kg/min) or moderate (0.9 mU/kg/min) hyperinsulinemia [8].…”
Section: Effects In Lean Healthy Individualsmentioning
confidence: 99%
“…Yet, studies that use experimental hyperinsulinemia to examine the vascular actions of insulin have shown inconsistent findings. Some of these studies reported enhanced limb blood flow in response to insulin stimulation [40,58,69,171], whereas others demonstrated either null effects or reduction in blood flow [8,80,120,191]. As a result, the prevailing concept that hyperinsulinemia induces vasodilation and improves blood flow may need to be reconsidered.…”
Section: Introductionmentioning
confidence: 99%
“…If so, these auxiliary properties could have important applications for patients with conditions such as hypertension, post-myocardial infarction, chronic kidney disease, heart failure and diabetes in whom elevated sympathetic activity and decreased vagal HR (heart rate) modulation are present, and are associated with increased risk of ventricular hypertrophy [52], impaired endothelium-dependent and -independent vasodilation [53][54][55], insulin resistance [56,57], arrhythmias [58] and premature mortality [59][60][61].…”
Section: Experimental Backgroundmentioning
confidence: 99%